Incidental Diagnosis of Ovarian Mucinous Cyst Adenocarcinoma during Emergency Caesarean Section - A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Mucinous cystadenocarcinoma contribute about 10 to 20 % of epithelial carcinoma ovaries. A large Mucinous cystadenocarcinoma about 15kg weight and about 25cm×15cm×10cm size was found during emergency caesarean section due to obstructed labor in a primi gravida with term pregnancy. Right sided salpingo-ovariotomy with the mass was done. Per-operative no evidence of metastasis, other ovary was healthy. Histopathological report confirmed the diagnosis of well differentiated mucinous cystadenocarcinoma .The patient was referred to the National Institute of Cancer Research & Hospital, Mohakhali, Dhaka. She was treated with 3 cycles chemotherapy (Inj.paclotaxel 250mg. 01+Inj.carboplatin 450mg×02 for 4 days 1st week, 3 days 2nd week, 2 days 3rd week). 3 months later, the patient was treated in Christian Medical College Vellore, Tamil Nadu, India, where interval debulking (total abdominal hysterectomy, left sided salpingo-oophorectomy with infra colic omentectomy) was done and another same 3 cycles chemotherapy was given. Further follow up in the same institute in India after 6 months revealed no abnormalities (C.T scan of the abdomen and pelvis -no evidence of intra abdominal adenopathy). Now the patient is symptom free for about two years (Last visit 3 months back). Key words: Mucinous cystadenocarcinoma; caesarean section; primi gravida; salpingooophorectomy; chemotherapy. DOI: 10.3329/bjog.v24i1.6325 Bangladesh J Obstet Gynaecol, 2009; Vol. 24(1) 32-35